Evgeny Alexandrovich Bragin (1954–2020) - Todd Katzner (Пернатые хищники и их охрана, 2021)
Evgeny Alexandrovich Bragin, a leading ornithologist and raptor biologist in Kazakhstan, passed away at the age of 66, from complications of COVID-19, on 25 August 2020 in Kostanay.